Efficiency and Equity: a Stated Preference Approach - Norman, Richard; Hall, J.; Street, D.; Viney, R. (John Wiley, 2013)
Outcome measurement in the economic evaluation of health care considers outcomes independent of to whom they accrue. This article reports on a discrete choice experiment designed to elicit population preferences regarding the allocation of health gain between hypothetical groups of potential patients. A random-effects probit model is estimated, and a technique for converting these results into equity weights for use in economic evaluation is adopted. On average, the modelling predicts a relatively high social value on health gains accruing to nonsmokers, carers, those with a low income and those with an expected age of death less than 45 years. Respondents tend to favour individuals with similar characteristics to themselves. These results challenge the conventional practice of assuming constant equity weighting. For decision makers, whether a formal equity weighting system represents an improvement on more informal approaches to weighing up equity and efficiency concerns remains uncertain.